Case Report: Simultaneous Resection of Bone Tumor and CAD/CAM Titanium Cranioplasty in Fronto-Orbital Region - Yashin, Konstantin S.; Ermolaev, Anton Yu.; Ostapyuk, Mikhail V.; Kutlaeva, Marina A.; Rasteryaeva, Marina V.; Mlyavykh, Sergey G.; Medyanik, Igor A. (Frontiers in Surgery, 2021)
Background: Simultaneous resection of bone tumors in the fronto-naso-orbital region is a great challenge due to the need for adequate reconstruction of the facial skeleton. Pre-operative virtual planning of resection margins and the simultaneous fabrication of the cranioplasty using computer-aided design/computer-aided manufacturing (CAD/CAM) technology could allow combining the tumor resection and cosmetic restoration steps into a single procedure. Methods: We present five consecutive cases of patients with bone tumors of the fronto-naso-orbital region. The indications for surgery included: (1) the presence of a major cosmetic defect; (2) progressive tumor growth. The histological examination revealed vascular malformation, hemangioma, and fibrous dysplasia in two cases. Tumor resection was performed with the help of a drilling template in form of a tumor. The computer-designed cranioplasty formed based on the non-involved side of the skull of the patient was manufactured. In one patient, the reconstruction was performed using two separate implants. Results: The position of the implant fits in with pre-operative planning in two cases; in those cases, the additional trimming of the implant or bone defect was required. Good cosmetic outcomes were noted in all patients, and no complications occurred. No repeat surgery was necessary. The template has proved to have high application potential. Conclusion: Simultaneous resection and CAD/CAM cranioplasty in the case of bone tumors in the fronto-orbital region is a promising technique with the aim of minimizing operation time and achieving a good esthetic outcome.